Electromagnetic interference shielding effectiveness of polyaniline-nickel oxide coated cenosphere composite film. (June 2017) - Bora, Pritom J.; Vinoy, K.J.; Ramamurthy, Praveen C.; Kishore,; Madras, Giridhar
Abstract: The solid waste material cenosphere (fly ash, by-product of thermal power plants) was nickel oxide nanoparticle coated (NiOC, core shell structure) by chemical heterogeneous precipitation and thermal reduction method. in situ synthesis of polyaniline (PANI) and NiOC composite (PNiOC) was carried out at -30±2 °C under nitrogen and characterized. The free standing films of as synthesized PNiOC composite were prepared by solution casting (followed by acid vapor treatment) and electromagnetic interference (EMI) shielding effectiveness (SE) was investigated in the J-band (5.8–8.2 GHz), X-band (8.2–12.4 GHz) and Ku-band (12.4–18 GHz). An average EMI SE of ~24 dB, ~27–24 dB, ~21 dB was observed for 81±3 μm thicker flexible free standing PNiOC film in the J, X and Ku-band respectively. Effective EMI shielding due to absorption (SEA ) was found to be dominant for PNiOC film. Unlike PANI emeraldine salt (ES) film, the EMI shielding due to absorption (SEA ) was found more than two times higher for PNiOC film. Due to the presence of NiOC hollow microspheres in PANI, the time average power of incident electromagnetic wave decreases resulting in an increase of EMI SE (SEA ). This film can be considered as a novel coating material for various applications such as unmanned vehicles, robotic and microwave engineering to protect against EMI. Highlights: Synthesis of NiO coated cenosphere (industrial waste) composite. Preparation of PANI-NiO-cenosphere composite and its film. High electromagnetic interference (EMI) shielding effectiveness of PANI-NiO-cenosphere composite film. The average EMI SE due to absorption of PANI-NiO-cenosphere composite film is dominant in J (5.8–8.2 GHz), X (8.2–12.4 GHz) and Ku (12.4–18 GHz) band.